2020
DOI: 10.1530/rep-20-0119
|View full text |Cite
|
Sign up to set email alerts
|

Obesity induction in adult zebrafish leads to negative reproduction and offspring effects

Abstract: Obesity is transgenerational epigenetic metabolic disturbance. Although the diet-induced obese (DIO) zebrafish model is well established, reproductive parameters and changes in offspring have not yet been evaluated. Thus, the aim of this study was to evaluate possible changes in reproductive parameters, embryos and offspring (F1) generated by the reproduction of diet-induced obese males and females. The adult zebrafish were divided into two groups receiving a balanced diet (Control group) or overfed (DIO group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…These methodological advantages have been exploited for developing a bioassay to evaluate the obesogenic properties of chemicals in zebrafish larvae [161]. Zebrafish models can also help assess specific windows of sensitivity during life as well as transgenerational effects of obesogens [168][169][170] and can be used to study the interaction between the diet composition and metabolic health effects promoted by subsequent chemical exposures [114,152,159,160,171]. Interesting recent research demonstrated that long-term dietary vitamin D deficiency promoted stunted growth and increased central adiposity via both adipocyte hypertrophy and hyperplasia in both visceral and subcutaneous depots [172].…”
Section: Danio Rerio (Zebrafish)mentioning
confidence: 99%
“…These methodological advantages have been exploited for developing a bioassay to evaluate the obesogenic properties of chemicals in zebrafish larvae [161]. Zebrafish models can also help assess specific windows of sensitivity during life as well as transgenerational effects of obesogens [168][169][170] and can be used to study the interaction between the diet composition and metabolic health effects promoted by subsequent chemical exposures [114,152,159,160,171]. Interesting recent research demonstrated that long-term dietary vitamin D deficiency promoted stunted growth and increased central adiposity via both adipocyte hypertrophy and hyperplasia in both visceral and subcutaneous depots [172].…”
Section: Danio Rerio (Zebrafish)mentioning
confidence: 99%
“…Decreased HSI in the FO group reveals that a high level of dietary n-3 PUFAs significantly reduced fat accumulation in the liver. It is well known that adult zebrafish suffer from hepatic adipose infiltration, which might influence reproduction and offspring (Virote et al, 2020). The liver with less fat tissue should be healthier, and the healthy liver might have a stronger ability to synthesize the proteins and lipids, such as the Vtg and Zp proteins required for gonadal development.…”
Section: Dietary N-3 Long-chain Polyunsaturated Fatty Acids Effected Growth Performancementioning
confidence: 99%
“…The damage caused by maternal obesity can be inherited for three generations (Andreas et al, 2019). In diet‐induced obese zebrafish model, the offspring display high rate of morphologic deformities and high level of plasma glucose and triglyceride, finally show 100% mortality at 60 days post fertilization (Virote et al, 2020). In our studies, the fries of moderate restriction group (1% feeding rate) show high quality, such as low rate of morphological deformities and high survival rate (Figure 3).…”
Section: Discussionmentioning
confidence: 99%